Inflow and outflow of human resources: Specific conditions of South East European countries - Blagica Novkovska; Violeta Milenkovska; Angela Milenkovska Klimoska (UTMS Journal of Economics, 2022)
Health and security crises could drastically influenece the balance of human resource supply and demand in national economies. Economies in the region of Southeastern Europe are strongly exposed to effects of the crises. Human resource managment in such periods for these countries must consider the effects of the crises on the flows of qualified people. Methododology of the study involves use of a mathematical model, providing precise quantitative analysis in the case of absence of drastic events. Effects of the emerging crisis are anticipated qualitatively based on the expected influence on the parameters of the model. In the present work balanced supply and demand model for human resources is proposed. The model was applied to the case of a specific numeric example for a group of occupations in Republic of North Macedonia connected with the qualifications provided by the vocational secondary education. Disbalance effects generated by security crisis are discussed consequently. Methods for coping with the effects of disbalance aiming at keeping the existing growth of job positions are also proposed
Keywords: C22; J24; 330; human resources supply and demand; security crisis